Pengaruh Total Quality Management (TQM) dan Budaya Organisasi terhadap Kinerja Karyawan - Suwarno, Suwarno; Aprianto, Ronal; Suberthi, Meta (Universitas muhammadiyah palembang, 2020)
This research is a quantitative study and the purpose of this study is to determine the effect of Total Quality Management (TQM) and Organizational Culture on Employee Performance at PT. Bank Mandiri (Persero) Tbk Lubuklinggau Branch Office. The research sample consisted of 72 employees and the data analysis used was regression, coefficient of determination test, t-test, and F test. Regression results were obtained: Y = 0.850 + 0.016X1+0.769X2. Meanwhile, the value of R square (R2) was 0.524 (52.4%), the remaining 47.7% was influenced by other variables not examined. TQM results did not significantly affect the Performance of Employees with tcount=0.461<ttable=1.667. Organizational Culture significantly affects Employee Performance with tcount=8.778>ttable=1.667. TQM and Organizational Culture significantly affect Employee Performance with Fcount = 38.031>Ftable=3.13. It was concluded that there was an influence of TQM and Organizational Culture on the Performance of Employees of PT. Bank Mandiri (Persero) Tbk Lubuklinggau Branch Office.